Influência do hálux valgo no desempenho físico e funcional de idosos - Nascimento, Washigton Santana (2018)
Introduction: The human foot is a complex body structure, maintaining the control of the posture, the maintenance of the balance and the execution of the movements. The foot becomes vulnerable to deformities with aging, and hallux valgus (HV) is one of the most prevalent. Objective: To identify the influence of the heavy and functional work of the elderly. Methods: This is a cross-sectional and descriptive study of a quantitative approach. 30 years divided into groups: group 1 (valgus group) and group 2 (no change in hallux). The evaluation instruments used were: a questionnaire with sociodemographic and clinical questions; Mini Mental State Examination (MMSE); Identification and graduation of HV; Instrumentation Short Physical Performance Battery (SPPB); Functional Test of Tandem March (MT) and Fall Efficiency Scale (FES-I). Results: The most severe statistic was the total SPPB score (p <0.0001) and the FES-I score (p = 0.04), but no difference in the functional test of TM (p = 0, 17). Conclusion: Hallux valgus can influence the physical performance (static balance, gait velocity and strength of the limbs) of the elderly, as well as increasing fear and risk of falling.